Successful project management - Richman, Larry L. (Larry Leon), 1955- (American Management Association, 2005)
Project management has emerged as the premier solution to today?s organizational challenges. Project managers deliver success by using a structured approach to project planning, sourcing, decision-making and control. Successful Project Management, Second Edition, is a comprehensive and up-to-date guide to virtually every aspect of managing your project?from initial planning to final review. Focusing on practical application, this course enables you to acquire the concepts and tools you need to plan, manage, and deliver project success. This edition delivers the knowledge, skills, and guidance managers need to lead today?s projects successfully and profitably.